Detailed therapeutic hypothermia protocol after cardiac arrest - Kızılaslan, Deniz; Erdoğan, Cem; Çiftçi, Bahadır; Ekinci, Mürsel (Galenos Yayıncılık, 2019)
Sudden cardiac arrest occurs in an average of 375,000 people every year in Europe (1). Cardiac arrest lasting five minutes or longer results in cerebral injury (1). In order to achieve better neurological results and improve outcomes, targeted temperature management (TTM) protocols have been developed, following clinical trials that showed good outcomes in out-of-hospital cardiac arrest (1,2). TTM protocols have been recommended in European guidelines (3).
Kardiyak arrest sonrası detaylı terapötik hipotermi protokolü
Keywords: Targeted Temperature Management; Protocol; Cardiac Arrest; Terapötik Hipotermi Yönetimi; Protokol; Kardiyak Arrest